Issues and Challenges of Accession to the GPA by Developing Economies: A Study of Thailand - Khoman, Sirilaksana (Journal of Malaysian and Comparative Law, 2011)
The World Trade Organisation’s Agreement on Government Procurement (GPA) has been in effect since 1st January 1996. Its purpose was to open up the government procurement market as much as possible to international competition. However, developing countries have been reluctant to consider membership in the GPA mainly due to fear that the local industry would be adversely affected by foreign competition. This paper examines the existing laws, regulations, procedures and practices regarding government procurement in Thailand, comparing them with major features of the 2006 Revision of the GPA. It looks at current procurement problems in Thailand, and assesses whether membership in the GPA would help alleviate these problems. It concludes that greater transparency in government procurement would benefit Thailand, but preparatory steps are needed to determine Thailand’s comparative advantage and assist domestic suppliers to adjust during the transition.